2023
DOI: 10.1249/mss.0000000000003280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Exercise-Based Rehabilitation on Long COVID: A Systematic Review and Meta-analysis

Chen Zheng,
Xiang-Ke Chen,
Cindy Hui-Ping Sit
et al.

Abstract: Purpose The number of persons living with post-coronavirus disease 2019 (COVID-19) conditions or long COVID continues to rise worldwide; however, the etiology and treatment of long COVID remain nebulous. Therefore, efficient, feasible, and cost-effective therapeutic strategies for a large population with long COVID remain warranted. Physical exercise-based rehabilitation is a promising strategy for long COVID, although its therapeutic effects remain to be determined. This systematic review and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Rehabilitation with physical activity is a promising strategy used in routine clinical practice, although its therapeutic effects are not yet clearly defined. The literature shows that it has a positive effect on the symptoms of dyspnoea, fatigue, depression, and quality of life [59].…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation with physical activity is a promising strategy used in routine clinical practice, although its therapeutic effects are not yet clearly defined. The literature shows that it has a positive effect on the symptoms of dyspnoea, fatigue, depression, and quality of life [59].…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with these findings, a recent meta-analysis including 23 studies totaling 1579 subjects with documented SARS-CoV-2 infection revealed that a program of PAbased rehabilitation may be an effective therapeutic option in patients with long-COVID, showing substantial benefits on most symptoms, particularly dyspnea, fatigue, depression, and capacity of performing physical exercise. 11 The Second Side of the Coin: Long-COVID and Risk of Physical Inactivity…”
Section: The First Side Of the Coin: Physical Inactivity And Risk Of ...mentioning
confidence: 99%
“…Physical exercise rehabilitation has also been shown to provide improvement of fatigue but it is essential to rule out conditions such as post-exertional malaise (PEM) and POTS as exercise may exacerbate symptoms and be harmful ( 41 , 48 , 51 ). A randomized controlled trial (RCT) examined functional versus aerobic exercise telerehabilitation programs in combination with breathing techniques to improve long COVID symptoms and demonstrated both improved quality of life and stress symptoms ( 54 ).…”
Section: Managementmentioning
confidence: 99%
“…However, functional exercise exhibited more significant results improving fatigue and functional performance ( 54 ). Physical exercise rehabilitation should be performed in a clinical setting with direct supervision to ensure patient safety ( 51 , 55 ).…”
Section: Managementmentioning
confidence: 99%